On Performatıve And Constatıve Constructıons - Adil Oglu, Shahbazli Tamerlan (Advances in Social Sciences Research Journal, 2018)
The article deals with the formation of the theory of speech act. It states the opinions of different linguistics about speech act such as J.Austin, C.Searle, etc. The article underlines that the theory of the stated problem in the linguistcs is related to the name of J.Austin. The author especially analyzes the essay by J.Austin “How to do things with words”. It underlines the division of speech acts such as locutive, illocutive, and perlocutive. The examples used in the article have been explained comprehensively in the article. J.Austin’s speech act theory has also been touched upon by the author.